Daughters at Risk: Analyzing the Impact of Maternal Son Preference on Stunting and Wasting in Indonesia - Adnan, Muhammad; Marwiyati, Marwiyati; Zurriyani, Zurriyani; Thahira, Zia (Jurnal Ilmiah Peuradeun, 2025)
Son preference remains prevalent in various communities, influencing intra-household resource allocation and potentially affecting child health outcomes. This study examines the impact of maternal son preference on stunting and wasting among children in Indonesia, utilizing data from the Indonesian Family Life Survey (IFLS) waves 4 and 5. Employing a logit regression model, the analysis incorporates various socioeconomic and demographic factors to estimate the effects of maternal son preference on child malnutrition. The findings indicate that while there is no significant correlation between maternal son preference and stunting incidence, a notable increase in the risk of wasting among boys and a reduction in wasting among girls were observed in households where mothers exhibited a son preference. These results underscore the complex interplay between gender biases and child health, highlighting the need for gender-sensitive health interventions. This study contributes to the literature on gender disparities in child health by providing empirical evidence on the nuanced effects of maternal son preference, offering critical insights for policymakers seeking to promote gender equity and improve child welfare in Indonesia.